Preparation method of micro-arc oxidation heat absorption coating
By adding cerium oxide and alumina-coated titanium dioxide nanoparticles to the microarc oxidation coating, the problem that the microarc oxidation coating does not have heat absorption function is solved, and the heat absorption performance of the coating is improved and the service life is extended.
Patent Information
- Application Number
- CN202411720328.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
The existing micro-arc oxidation coating does not have the heat absorption function, which leads to the heat absorption coating being easily shedded and wearable, and greatly reduces its service life.
By adding cerium oxide during the microarc oxidation process, a composite oxide coating containing cerium elements is formed, and alumina-coated titanium dioxide nanoparticles are added to the traditional sealing solution, the light absorption and photothermal conversion characteristics of the coating are enhanced.
The heat absorption performance of the coating is improved, so that it can absorb more photons, and the service life of the coating is extended by improving the photothermal conversion efficiency.
Smart Images

Figure CN119663397A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of micro-arc oxidation coating preparation, and in particular to a method for preparing a micro-arc oxidation heat-absorbing coating. Background Art
[0002] The micro-arc oxidation process introduces the working area from the Faraday area of ordinary anodizing to the high-voltage discharge area, overcoming the defects of hard anodizing and greatly improving the comprehensive performance of the film. The micro-arc oxidation film is firmly bonded to the substrate, has a dense structure, high toughness, and has good wear resistance, corrosion resistance, high temperature impact resistance, and electrical insulation.
[0003] The micro-arc oxidation process introduces the working area from the Faraday area of ordinary anodizing to the high-voltage discharge area, overcoming the defects of hard anodizing and greatly improving the comprehensive performance of the film layer. The micro-arc oxidation coating has a strong bond with the substrate, a dense structure, high toughness, good wear resistance, corrosion resistance, high temperature impact resistance and electrical insulation. However, the existing micro-arc oxidation coating does not have a heat absorption function, so the micro-arc oxidation technology cannot solve the problem that the heat absorption coating is easy to fall off and easy to wear, resulting in a greatly reduced service life.
[0004] Therefore, it is necessary to design a method for preparing a micro-arc oxidation heat-absorbing coating to solve the problem that the traditional micro-arc oxidation method cannot prepare the heat-absorbing coating. Summary of the invention
[0005] In view of this, the present invention proposes a method for preparing a micro-arc oxidation heat-absorbing coating, aiming to solve the problem that the traditional micro-arc oxidation method cannot prepare the heat-absorbing coating.
[0006] The present invention provides a method for preparing a micro-arc oxidation heat-absorbing coating, comprising:
[0007] S1. Use sandpaper to polish the surface of the aluminum alloy sample, soak the polished aluminum alloy sample in an organic solvent for 10-15 minutes, then rinse it with deionized water to remove oil and impurities on the surface, and then put it in an oven to dry at 60-80° C. for 1-2 hours to obtain a pretreated aluminum alloy sample;
[0008] S2, using the pretreated aluminum alloy as an anode, fixing it on the fixture of the micro-arc oxidation equipment, using a stainless steel plate as a cathode, placing it in an electrolytic cell filled with an electrolyte containing cerium oxide powder, adjusting the micro-arc oxidation process parameters, and performing micro-arc oxidation;
[0009] S3. After the micro-arc oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in deionized water, and the cleaned sample is placed in an oven for drying to obtain an aluminum alloy sample with a micro-arc oxidation coating;
[0010] S4, immersing the aluminum alloy sample with the micro-arc oxidation coating in the prepared sealing solution. After the immersion is completed, the aluminum alloy sample with the micro-arc oxidation coating is naturally dried, and then cured;
[0011] S5. After the curing is completed, the aluminum alloy sample with the micro-arc oxidation coating is taken out, rinsed with deionized water, and dried to obtain the aluminum alloy sample with the micro-arc oxidation heat-absorbing coating.
[0012] Furthermore, the electrolyte containing cerium oxide powder in step S2 includes: 12-36 parts of basic silicate electrolyte, 1-5 parts of sodium citrate, and 5-20 parts of cerium oxide powder.
[0013] Furthermore, the preparation method of the electrolyte containing cerium oxide powder in step S2 is:
[0014] Sodium citrate is added to the basic silicate electrolyte and stirred evenly, and cerium oxide powder is slowly added to the basic electrolyte while stirring to fully disperse it, thereby obtaining the electrolyte containing cerium oxide powder.
[0015] Furthermore, the method for preparing the sealing solution in step S4 is:
[0016] Dissolve the silicone resin in an appropriate amount of organic solvent and deionized water to prepare a basic sealing solution with a concentration of 10%-30%;
[0017] Polyethylene glycol is added to the basic sealing solution, and then the alumina-coated titanium dioxide nanoparticles are slowly added to the basic sealing solution, and stirred with a magnetic stirrer or a mechanical stirrer to make it evenly dispersed, and the pH value of the solution is adjusted to between 7 and 9 with ammonia water or dilute hydrochloric acid to obtain the sealing solution.
[0018] Furthermore, the sealing solution comprises: 100 parts of a basic sealing solution, 5-20 parts of alumina-coated titanium dioxide nanoparticles, and 0.1-0.4 parts of polyethylene glycol.
[0019] Furthermore, the micro-arc oxidation process parameters in step S2 are: voltage of 300-500V, current density of 10-30A / dm 2 , the pulse frequency is 500-1000Hz, the duty cycle is 20%-50%, and the oxidation time is 10-60 minutes.
[0020] Furthermore, during the micro-arc oxidation process, the electrolyte temperature and pH value are detected in real time to ensure that the electrolyte temperature is between 20-40°C and the electrolyte pH is between 9-11.
[0021] Furthermore, the specific polishing method in step S1 is: using 200 mesh, 400 mesh, 600 mesh and 800 mesh sandpaper to polish the surface of the aluminum alloy sample in sequence.
[0022] Furthermore, before performing the sealing treatment in step S4, the aluminum alloy sample to be sealed is pretreated: determine whether there is oil stain on the surface of the aluminum alloy sample. If there is oil stain, wipe it clean with acetone or alcohol, then rinse it with deionized water, and put it in an oven to dry.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: by adding cerium oxide during the micro-arc oxidation process, a composite oxide coating containing cerium elements can be formed on the surface of the aluminum alloy, and the cerium oxide is partially embedded in the microstructure of the coating, which changes the energy band structure of the coating, so that the coating can absorb more photons that were originally unable to be absorbed; at the same time, by adding alumina-coated titanium dioxide nanoparticles in the traditional sealing solution, the alumina-coated titanium dioxide nanoparticles are evenly distributed in the voids of the composite oxide coating, and titanium dioxide itself has good light absorption and photothermal conversion properties, which can increase the overall light absorption area and photothermal conversion efficiency of the coating; and during the multiple reflections and scattering processes of light in the pores of the coating, the light will repeatedly interact with the titanium dioxide particles, thereby increasing the probability of light absorption, and at the same time, the addition of cerium oxide allows the coating to absorb more photons, and the combination of the two further improves the heat absorption performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0025] Figure 1 A flow chart of a method for preparing a micro-arc oxidation heat-absorbing coating provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0027] Reference Figure 1As shown, in some embodiments of the present application, a method for preparing a micro-arc oxidation heat-absorbing coating comprises:
[0028] S1. Use sandpaper to polish the surface of the aluminum alloy sample, soak the polished aluminum alloy sample in an organic solvent for 10-15 minutes, then rinse it with deionized water to remove oil and impurities on the surface, and then put it in an oven to dry at 60-80° C. for 1-2 hours to obtain a pretreated aluminum alloy sample;
[0029] S2, using the pretreated aluminum alloy as an anode, fixing it on the fixture of the micro-arc oxidation equipment, using a stainless steel plate as a cathode, placing it in an electrolytic cell filled with an electrolyte containing cerium oxide powder, adjusting the micro-arc oxidation process parameters, and performing micro-arc oxidation;
[0030] S3. After the micro-arc oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in deionized water, and the cleaned sample is placed in an oven for drying to obtain an aluminum alloy sample with a micro-arc oxidation coating;
[0031] S4, immersing the aluminum alloy sample with the micro-arc oxidation coating in the prepared sealing solution. After the immersion is completed, the aluminum alloy sample with the micro-arc oxidation coating is naturally dried, and then cured;
[0032] S5. After the curing is completed, the aluminum alloy sample with the micro-arc oxidation coating is taken out, rinsed with deionized water, and dried to obtain the aluminum alloy sample with the micro-arc oxidation heat-absorbing coating.
[0033] In the present invention, the particle size of the cerium oxide is 20-100 nanometers; the purity is preferably 99%.
[0034] The immersion time of the polished aluminum alloy sample in step S1 of the present invention is preferably 13-15 minutes, more preferably 15 minutes; the organic solvent is preferably acetone or alcohol, more preferably alcohol; the oven temperature is preferably 70°C, and the drying time is preferably 2 hours.
[0035] In step S3 of the present invention, the oven temperature is preferably 60-100° C., more preferably 100° C.; the drying time is preferably 2-4 hours, more preferably 4 hours.
[0036] In step S4 of the present invention, the aluminum alloy sample with the micro-arc oxidation coating is immersed in the prepared sealing solution, wherein the immersion time is preferably 30-120 minutes, and more preferably 120 minutes; the natural drying time is preferably 10-20 minutes, and more preferably 20 minutes; the curing temperature is preferably 120-180°C, and more preferably 180°C; the curing time is preferably 1-3 hours, and more preferably 3 hours.
[0037] In step S5 of the present invention, the oven temperature is preferably 80-100° C., more preferably 100° C.; the drying time is 1-2 hours, more preferably 2 hours.
[0038] It is understandable that the addition of cerium oxide during the micro-arc oxidation process can form a composite oxide coating containing cerium element on the surface of the aluminum alloy. The cerium oxide is partially embedded in the microstructure of the coating, which changes the energy band structure of the coating and enables the coating to absorb more photons that were originally unable to be absorbed. At the same time, alumina-coated titanium dioxide nanoparticles are added to the traditional sealing solution, so that the alumina-coated titanium dioxide nanoparticles are evenly distributed in the voids of the composite oxide coating. Titanium dioxide itself has good light absorption and photothermal conversion properties, which can increase the overall light absorption area and photothermal conversion efficiency of the coating. Moreover, during the multiple reflections and scatterings of light in the pores of the coating, it will repeatedly interact with the titanium dioxide particles, increasing the probability of light absorption. At the same time, the addition of cerium oxide enables the coating to absorb more photons. The combination of the two further improves the heat absorption performance of the coating.
[0039] In some embodiments of the present application, the electrolyte containing cerium oxide powder in step S2 includes: 12-36 parts of basic silicate electrolyte, 1-5 parts of sodium citrate, and 5-20 parts of cerium oxide powder, preferably 24-36 parts of basic electrolyte, 3-5 parts of sodium citrate, and 10-20 parts of cerium oxide powder, and further preferably, 36 parts of basic electrolyte, 5 parts of sodium citrate, and 20 parts of cerium oxide powder.
[0040] Specifically, the basic silicate electrolyte is an electrolyte of an existing silicate system, which consists of sodium silicate, sodium hydroxide and deionized water.
[0041] In some embodiments of the present application, the method for preparing the electrolyte containing cerium oxide powder in step S2 is: adding sodium citrate to the basic silicate electrolyte and stirring evenly, slowly adding the cerium oxide powder to the basic electrolyte and stirring at the same time to fully disperse it, so as to obtain the electrolyte containing cerium oxide powder.
[0042] It is understandable that sodium citrate can be used as a dispersant to evenly disperse the added cerium oxide powder into the electrolyte, thereby improving the uniformity of the distribution of the cerium element in the layer.
[0043] In some embodiments of the present application, the method for preparing the sealing solution described in step S4 is: dissolving the silicone resin in an appropriate amount of an organic solvent and deionized water to prepare a basic sealing solution with a concentration of 10%-30%; adding polyethylene glycol to the basic sealing solution, and then slowly adding the alumina-coated titanium dioxide nanoparticles to the basic sealing solution, while stirring with a magnetic stirrer or a mechanical stirrer to make it evenly dispersed, and adjusting the pH value of the solution to between 7-9 with ammonia water or dilute hydrochloric acid to obtain the sealing solution.
[0044] The concentration of the basic sealing solution is preferably 20-30%, and more preferably 30%;
[0045] The alumina-coated titanium dioxide nanoparticles are prepared by adopting the preparation method disclosed in publication number CN114106589A.
[0046] It can be understood that polyethylene glycol as a dispersant can make the alumina-coated titanium dioxide nanoparticles evenly dispersed in the sealing solution, improve the distribution uniformity of the alumina-coated titanium dioxide nanoparticles, and the alumina-coated titanium dioxide nanoparticles greatly improve their bonding ability with the coating due to the presence of aluminum oxide on their surface. At the same time, the alumina coating layer improves the dispersibility of the titanium dioxide nanoparticles and reduces the agglomeration phenomenon between particles, so that more titanium dioxide particle surfaces can be exposed to light, thereby increasing the absorption intensity of light and allowing more photons to be absorbed and utilized.
[0047] In some embodiments of the present application, the sealing solution comprises: 100 parts of a basic sealing solution, 5-20 parts of alumina-coated titanium dioxide nanoparticles, and 0.1-0.4 parts of polyethylene glycol.
[0048] The sealing solution is preferably: 100 parts of basic sealing solution, 10-20 parts of alumina-coated titanium dioxide nanoparticles and 0.2-0.4 parts of polyethylene glycol; further preferably: 100 parts of basic sealing solution, 20 parts of alumina-coated titanium dioxide nanoparticles and 0.4 parts of polyethylene glycol.
[0049] In some embodiments of the present application, the micro-arc oxidation process parameters in step S2 are: voltage of 300-500V, current density of 10-30A / dm2, pulse frequency of 500-1000Hz, duty cycle of 20%-50%, oxidation time of 10-60 minutes; preferably: voltage of 400-500V, current density of 20-30A / dm2 2 , the pulse frequency is 800-1000Hz, the duty cycle is 30%-50%, and the oxidation time is 40-60 minutes; further preferably: voltage 500V, current density 30A / dm 2, the pulse frequency is 1000 Hz, the duty cycle is 50%, and the oxidation time is 60 minutes.
[0050] In some embodiments of the present application, the electrolyte temperature and pH value are detected in real time during the micro-arc oxidation process to ensure that the electrolyte temperature is between 20-40° C. and the electrolyte pH is between 9-11.
[0051] Specifically, the temperature can be maintained stable by a cooling circulation system; the pH value can be adjusted by adding a solution such as sodium hydroxide or hydrochloric acid to the electrolyte.
[0052] It is understandable that ensuring that the electrolyte temperature is between 20-40°C and the electrolyte pH is between 9-11 helps to generate a more uniform and dense oxide film. Too high or too low temperature and pH value outside the range may lead to defects in the film layer, such as increased porosity and uneven hardness. At the same time, under the conditions of 20-40°C and pH 9-11, the film layer can grow at a relatively stable and appropriate rate to achieve the expected thickness requirements. If the temperature is too high or the pH value is not appropriate, the film layer may grow too fast or too slow, making it difficult to accurately control the thickness. In addition, the appropriate pH range helps to maintain the chemical stability of the various components in the electrolyte, preventing them from excessive decomposition, precipitation or other chemical reactions, thereby ensuring the effectiveness and consistency of the electrolyte throughout the micro-arc oxidation process.
[0053] In some embodiments of the present application, the specific polishing method in step S1 is: polishing the surface of the aluminum alloy sample using 200 mesh, 400 mesh, 600 mesh and 800 mesh sandpaper in sequence.
[0054] It is understandable that by gradually using sandpaper of different meshes for polishing, the cleanliness and roughness of the aluminum alloy surface are effectively controlled, which helps to enhance the bonding force between the oxide film and the aluminum alloy substrate. During the micro-arc oxidation process, the oxide film grows in situ on the surface of the aluminum alloy. A good surface state can form a tighter chemical bond and mechanical interlocking between the oxide film and the substrate. Moreover, the sequential polishing of sandpaper of different meshes makes the surface state of the aluminum alloy more uniform. This uniform surface can guide the uniform growth of the oxide film during the micro-arc oxidation process.
[0055] In some embodiments of the present application, before performing the sealing treatment in step S4, the aluminum alloy sample to be sealed is pretreated: determine whether there is oil stain on the surface of the aluminum alloy sample. If there is oil stain, wipe it clean with acetone or alcohol, then rinse it with deionized water, and then put it in an oven to dry.
[0056] Specifically, when oil stains are present, wipe with acetone or alcohol, then rinse with deionized water, and then dry in an oven at 60-80°C for 30-60 minutes.
[0057] It is understandable that oil stains will form an isolation layer between the sealing material and the coating, which will prevent the sealing material from penetrating into the pores of the coating well, and from forming effective chemical bonds or physical adsorption with the coating surface. The presence of impurities will cause abnormal blockage of the coating pores during the sealing process. When there is residual moisture on the surface, the sealing material may be diluted, agglomerated, and other problems may occur during the sealing process.
[0058] Example 1
[0059] S1. The surface of the prepared aluminum alloy sample is polished with 200 mesh, 400 mesh, 600 mesh, and 800 mesh sandpaper in turn. The polished aluminum alloy sample is soaked in an acetone solution for 10 minutes, then rinsed with deionized water to remove surface oil and impurities, and then placed in an oven to dry at 70°C for 2 hours for use.
[0060] S2, taking 12 parts of a basic silicate electrolyte, adding 1 part of sodium citrate to the basic silicate electrolyte and mixing evenly, then slowly adding 5 parts of cerium oxide powder while stirring to fully disperse it to obtain an electrolyte;
[0061] S3. Add the prepared electrolyte into the electrolytic cell, use the treated aluminum alloy sample as the anode, fix it on the fixture of the micro-arc oxidation equipment, ensure that the sample is in full contact with the electrolyte, and make the current evenly distributed on the sample surface. Use the stainless steel plate as the cathode and put it into the electrolytic cell filled with the electrolyte. Adjust the electrolysis parameters so that the voltage is 300V and the current density is 10A / dm 2 The pulse frequency is 500 Hz, the duty cycle is 20%, and the oxidation time is 10 minutes. During the oxidation process, the temperature and pH value of the electrolyte are monitored in real time to ensure that the electrolyte temperature is between 20-40°C. At the same time, the pH value is adjusted by adding sodium hydroxide or hydrochloric acid solutions to ensure that the pH value of the electrolyte is between 9-11.
[0062] S4. After the oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in flowing deionized water for 10 minutes to remove the residual electrolyte and impurities on the surface, and then dried at 60°C for 2 hours for standby use;
[0063] S5. Dissolve the silicone resin in ethanol solvent and deionized water to prepare a solution with a concentration of 10%, take 100 parts of the prepared solution, add 0.1 parts of polyethylene glycol thereto and stir evenly, then slowly add 5 parts of alumina-coated titanium dioxide nanoparticles, and stir with a magnetic stirrer or a mechanical stirrer to make them evenly dispersed, and then adjust the pH value of the solution to between 7 and 9 by dropping ammonia water or dilute hydrochloric acid to obtain a sealing solution;
[0064] S6. Wipe the oxidized aluminum alloy sample with acetone to remove impurities and oil stains, then dry it in an oven at 80° C. for 30 minutes, and then immerse it in the prepared sealing solution to ensure that the aluminum alloy sample is completely immersed for 30 minutes;
[0065] S7. After the impregnation is completed, the aluminum alloy sample is taken out, dried naturally for 10 minutes, excess solution on the surface is removed, and then placed in an oven for curing for 1 hour at a curing temperature of 120° C. to obtain an aluminum alloy sample having the micro-arc oxidation heat-absorbing coating.
[0066] Example 2
[0067] S1. The surface of the prepared aluminum alloy sample was polished with 200 mesh, 400 mesh, 600 mesh, and 800 mesh sandpaper in turn. The polished aluminum alloy sample was soaked in an alcohol solution for 13 minutes, then rinsed with deionized water to remove surface oil and impurities, and then placed in an oven to dry at 70°C for 2 hours for use.
[0068] S2, taking 24 parts of a basic silicate electrolyte, adding 3 parts of sodium citrate to the basic silicate electrolyte and mixing evenly, then slowly adding 15 parts of cerium oxide powder while stirring to fully disperse it to obtain an electrolyte;
[0069] S3. Add the prepared electrolyte into the electrolytic cell, use the treated aluminum alloy sample as the anode, fix it on the fixture of the micro-arc oxidation equipment, ensure that the sample is fully in contact with the electrolyte, and make the current evenly distributed on the surface of the sample. Use the stainless steel plate as the cathode and put it into the electrolytic cell filled with the electrolyte. Adjust the electrolysis parameters so that the voltage is 400V and the current density is 20A / dm 2 The pulse frequency is 800 Hz, the duty cycle is 40%, and the oxidation time is 30 minutes. During the oxidation process, the temperature and pH value of the electrolyte are monitored in real time to ensure that the electrolyte temperature is between 20-40°C. At the same time, the pH value is adjusted by adding sodium hydroxide or hydrochloric acid solutions to ensure that the pH value of the electrolyte is between 9-11.
[0070] S4. After the oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in flowing deionized water for 10 minutes to remove the residual electrolyte and impurities on the surface, and then dried at 80°C for 3 hours for standby use;
[0071] S5. Dissolve the silicone resin in ethanol solvent and deionized water to prepare a solution with a concentration of 20%, take 100 parts of the prepared solution, add 0.2 parts of polyethylene glycol thereto and stir evenly, then slowly add 15 parts of alumina-coated titanium dioxide nanoparticles, and stir with a magnetic stirrer or a mechanical stirrer to make them evenly dispersed, and then adjust the pH value of the solution to between 7 and 9 by dropping ammonia water or dilute hydrochloric acid to obtain a sealing solution;
[0072] S6. Wipe the oxidized aluminum alloy sample with acetone to remove impurities and oil stains, then dry it in an oven at 80° C. for 30 minutes, and then immerse it in the prepared sealing solution to ensure that the aluminum alloy sample is completely immersed for 30 minutes;
[0073] S7. After the impregnation is completed, the aluminum alloy sample is taken out, dried naturally for 15 minutes, excess solution on the surface is removed, and then placed in an oven for curing for 2 hours at a curing temperature of 140° C. to obtain an aluminum alloy sample having the micro-arc oxidation heat-absorbing coating.
[0074] Example 3
[0075] S1. The surface of the prepared aluminum alloy sample was polished with 200 mesh, 400 mesh, 600 mesh, and 800 mesh sandpaper in turn. The polished aluminum alloy sample was soaked in an alcohol solution for 15 minutes, then rinsed with deionized water to remove surface oil and impurities, and then placed in an oven to dry at 70°C for 2 hours for use.
[0076] S2, taking 36 parts of a basic silicate electrolyte, adding 5 parts of sodium citrate to the basic silicate electrolyte and mixing evenly, then slowly adding 20 parts of cerium oxide powder while stirring to fully disperse it to obtain an electrolyte;
[0077] S3. Add the prepared electrolyte into the electrolytic cell, use the treated aluminum alloy sample as the anode, fix it on the fixture of the micro-arc oxidation equipment, ensure that the sample is fully in contact with the electrolyte, and make the current evenly distributed on the surface of the sample. Use the stainless steel plate as the cathode and put it into the electrolytic cell filled with the electrolyte. Adjust the electrolysis parameters so that the voltage is 500V and the current density is 30A / dm 2 The pulse frequency is 1000 Hz, the duty cycle is 50%, and the oxidation time is 60 minutes. During the oxidation process, the temperature and pH value of the electrolyte are monitored in real time to ensure that the electrolyte temperature is between 20-40°C. At the same time, the pH value is adjusted by adding sodium hydroxide or hydrochloric acid solutions to ensure that the pH value of the electrolyte is between 9-11.
[0078] S4. After the oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in flowing deionized water for 10 minutes to remove the residual electrolyte and impurities on the surface, and then dried at 100°C for 4 hours for standby use;
[0079] S5. Dissolve the silicone resin in ethanol solvent and deionized water to prepare a solution with a concentration of 30%, take 100 parts of the prepared solution, add 0.4 parts of polyethylene glycol thereto and stir evenly, then slowly add 20 parts of alumina-coated titanium dioxide nanoparticles, and stir with a magnetic stirrer or a mechanical stirrer to make them evenly dispersed, and then adjust the pH value of the solution to between 7 and 9 by dropping ammonia water or dilute hydrochloric acid to obtain a sealing solution;
[0080] S6. Wipe the oxidized aluminum alloy sample with acetone to remove impurities and oil stains, then dry it in an oven at 80° C. for 30 minutes, and then immerse it in the prepared sealing solution to ensure that the aluminum alloy sample is completely immersed for 120 minutes;
[0081] S7. After the impregnation is completed, the aluminum alloy sample is taken out, dried naturally for 20 minutes, excess solution on the surface is removed, and then placed in an oven for curing for 3 hours at a curing temperature of 180° C. to obtain an aluminum alloy sample having the micro-arc oxidation heat-absorbing coating.
[0082] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented on one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) containing computer-usable program codes.
[0083] The present application is described with reference to flowcharts and / or block diagrams of methods, devices (systems) and computer program products according to embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0084] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.
[0085] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a micro-arc oxidation heat-absorbing coating, characterized in that: include: S1. Use sandpaper to polish the surface of the aluminum alloy sample, soak the polished aluminum alloy sample in an organic solvent for 10-15 minutes, then rinse it with deionized water to remove oil and impurities on the surface, and then put it in an oven to dry at 60-80° C. for 1-2 hours to obtain a pretreated aluminum alloy sample; S2, using the pretreated aluminum alloy as an anode, fixing it on the fixture of the micro-arc oxidation equipment, using a stainless steel plate as a cathode, placing it in an electrolytic cell filled with an electrolyte containing cerium oxide powder, adjusting the micro-arc oxidation process parameters, and performing micro-arc oxidation; S3. After the micro-arc oxidation is completed, the aluminum alloy sample is immediately taken out from the electrolyte, rinsed in deionized water, and the cleaned sample is placed in an oven for drying to obtain an aluminum alloy sample with a micro-arc oxidation coating; S4, immersing the aluminum alloy sample with the micro-arc oxidation coating in the prepared sealing solution. After the immersion is completed, the aluminum alloy sample with the micro-arc oxidation coating is naturally dried, and then cured; S5. After the curing is completed, the aluminum alloy sample with the micro-arc oxidation coating is taken out, rinsed with deionized water, and dried to obtain the aluminum alloy sample with the micro-arc oxidation heat-absorbing coating.
2. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: The electrolyte containing cerium oxide powder in step S2 includes: 12-36 parts of basic silicate electrolyte, 1-5 parts of sodium citrate, and 5-20 parts of cerium oxide powder.
3. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 2, characterized in that: The method for preparing the electrolyte containing cerium oxide powder in step S2 is: Sodium citrate is added to the basic silicate electrolyte and stirred evenly, and cerium oxide powder is slowly added to the basic electrolyte while stirring to fully disperse it, thereby obtaining the electrolyte containing cerium oxide powder.
4. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: The method for preparing the sealing solution in step S4 is: Dissolve the silicone resin in an appropriate amount of organic solvent and deionized water to prepare a basic sealing solution with a concentration of 10%-30%; Polyethylene glycol is added to the basic sealing solution, and then the alumina-coated titanium dioxide nanoparticles are slowly added to the basic sealing solution, and stirred with a magnetic stirrer or a mechanical stirrer to make it evenly dispersed, and the pH value of the solution is adjusted to between 7 and 9 with ammonia water or dilute hydrochloric acid to obtain the sealing solution.
5. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 4, characterized in that: The sealing solution comprises: 100 parts of a basic sealing solution, 5-20 parts of titanium dioxide nanoparticles coated with aluminum oxide, and 0.1-0.4 parts of polyethylene glycol.
6. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: The micro-arc oxidation process parameters in step S2 are: voltage of 300-500V, current density of 10-30A / dm 2 , the pulse frequency is 500-1000Hz, the duty cycle is 20%-50%, and the oxidation time is 10-60 minutes.
7. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: During the micro-arc oxidation process, the electrolyte temperature and pH value are detected in real time to ensure that the electrolyte temperature is between 20-40°C and the electrolyte pH is between 9-11.
8. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: The specific grinding method in step S1 is: using 200 mesh, 400 mesh, 600 mesh and 800 mesh sandpaper to grind the surface of the aluminum alloy sample in sequence.
9. The method for preparing a micro-arc oxidation heat-absorbing coating according to claim 1, characterized in that: Before performing the sealing treatment in step S4, the aluminum alloy sample to be sealed is pretreated: determine whether there is oil stain on the surface of the aluminum alloy sample. If there is oil stain, wipe it clean with acetone or alcohol, then rinse it with deionized water, and put it in an oven to dry.
Citation Information
Patent Citations
Micro-arc oxidation process for titanium alloy with high absorbance
CN112981494A
Preparation method of 7050 aluminum alloy surface micro-arc oxidation ceramic film layer
CN113913893A
Method for coating compact aluminum oxide film on surface of titanium dioxide particle
CN114106589A